Effect of liposome binding antisense oligonucleotide BP1003 on albumin-bound paclitaxel sensitivity in pancreatic cancer cells by inhibiting STAT3 - FU Hua, ZHOU Guochao, CAI Rongmin, SONG Xin, YANG Dinghua (Zhongguo aizheng zazhi)
Background and purpose: The resistance of pancreatic cancer to albumin-bound paclitaxel affects the therapeutic effect and prognosis. Signal transducer and activator of transcription 3 (STAT3) is one of the important molecules regulating the chemotherapy sensitivity of cancer cells. The liposome BP1003 targeting the antisense oligonucleotide of STAT3 mRNA can inhibit the expression of STAT3 and increase the chemotherapy sensitivity. However, the effect of BP1003 on the sensitivity of pancreatic cancer cells to albumin-bound paclitaxel remains unclear. The purpose of this study was to investigate the effects of liposome binding antisense oligonucleotide BP1003 on albumin-bound paclitaxel sensitivity in pancreatic cancer cells by inhibiting STAT3. Methods: Pancreatic cancer cell lines PANC-1 and ASPC-1 were cultured. They were divided into control group (without drugs), BP1003 group (200 μg/mL BP1003 intervention), different concentrations of albumin-bound paclitaxel group (5, 10, 20 nmol/L albumin-bound paclitaxel intervention), BP1003+different concentrations of albumin-bound paclitaxel group (200 μg/mL BP1003 combined with 5, 10, 20 nmol/L albumin-bound paclitaxel intervention). The proliferation viability, apoptotic rate and the protein expression levels of STAT3, STAT4, STAT6, Bcl-2, Bax and c-Myc were detected. The transplanted tumor model was established by subcutaneous injection of PANC-1 and ASPC-1 cell suspension in nude mice, which were divided into control group (normal saline intervention), BP1003 group (25 mg/kg BP1003 intervention, once every 2 weeks) and albumin-bound paclitaxel group (10 mg/kg albumin-bound paclitaxel, once a week), BP1003+albumin-bound paclitaxel group (25 mg/kg BP1003 intervention, once every 2 weeks combined with 10 mg/kg albumin-bound paclitaxel, once a week). Four weeks later, the graft volume and mass were measured, and the protein expression levels of STAT3, Bcl-2, Bax and c-Myc were detected. Results: The apoptotic rate and the protein expression levels of Bax of PANC-1 and ASPC-1 cells in BP1003 group and albumin-bound paclitaxel group were higher than those in the control group, while the proliferation viability and protein expression levels of STAT3, Bcl-2 and c-Myc were lower than those in control group (P<0.05). There was no significant difference in the expression levels of STAT4 and STAT6 in PANC-1 and ASPC-1 cells between BP1003 group and the control group (P>0.05). The apoptotic rate and the protein expression levels of Bax of PANC-1 and ASPC-1 cells in BP1003+different concentrations of albumin-bound paclitaxel groups were higher than those in different concentrations of albumin-bound paclitaxel groups, and the proliferation viability and protein expression levels of STAT3, Bcl-2 and c-Myc were lower than those in different concentrations of albumin-bound paclitaxel groups (P <0.05). The volume and mass of transplanted tumor and the protein expression levels of STAT3, Bcl-2 and c-Myc of nude mice in BP1003 group, albumin-bound paclitaxel group and BP1003+albumin-bound paclitaxel group were all lower compared with the control group, the protein expression level of Bax was higher compared with the control group (P<0.05), and the above changes in BP1003+albumin-bound paclitaxel group were more significant compared with BP1003 and albumin-bound paclitaxel group. Conclusion: BP1003 increases the sensitivity of pancreatic cancer cells to albumin-bound paclitaxel by inhibiting the expression of STAT3.